Análisis a la calidad de atención al cliente en la Microempresa Cyber y Multiservicios ML - Mora Parraga, Karla Romina (2021)
Today, the quality of customer service within a company demonstrates a competitive advantage and success in performance, which shows the level of customer satisfaction with the product or service that was delivered. To know the needs and expectations of customers, it is important to listen to their opinions and relate them to the service provided in general. The care provided has a great influence on them, because precisely they are the ones who decide whether to stay or leave, a quality of service is essential to retain the company with customers because they are going to advertise by recommending the products and services to other people. . The investigation called "Analysis of the Quality of Customer Service in Cyber and Multiservices ML" aimed to analyze the factors that cause an inadequate quality of customer service in said establishment and how the deficiency of staff affects the company, it was applied a descriptive research The existing problems in the Cyber and Multiservices ML were addressed based on the quality of customer service, the same that appear in the development. The methodology used in this study was qualitative and quantitative, the techniques and instruments used to collect more information were: an interview with the owner of a micro-business and a survey prepared for customers who visit the place, obtaining results that allowed to reach a general conclusion of the present case study, which was supported with bibliographic references, these helped to understand in a scientific way the depth of this research.